Impacts of burrowing sandprawns (Kraussillichirus kraussi) on water quality, phytoplankton and pelagic bacterial assemblages - De Cerff, Carla (Department of Biological Sciences, 2023)
Coastal environments are among the most threatened ecosystems globally, with water quality degradation constituting a major scientific and management issue that requires addressing. Burrowing sandprawns (Kraussillichirus kraussi) have been shown in past research to improve water quality by removing microalgae from the water column. Their burrows are thought to act as biofiltration systems, with water-borne phytoplankton particles being adsorbed onto burrow walls during bi-directional water pumping. However, not much is known about ecological repercussions of this hypothesised mechanism and whether it indiscriminately impacts all microorganisms in the water column. This issue forms the foundation of my research, which aimed to experimentally determine whether potential filtration effects of sandprawns are consistent across pelagic bacterial and phytoplankton assemblages or whether there are any discriminatory responses. Findings demonstrated that increasing sandprawn density did not significantly reduce the abundance of bacterial water quality indicators (Escherichia coli and total heterotrophic bacteria). However, sandprawns were found to reduce the abundance of phytoplankton cells. At the end of the experiment, the relative abundance of phytoplankton in the controls were 1.9 times higher relative to the 100% treatment. Similarly, the concentrations of nitrite were 17.7 times higher in controls relative to 100% treatment at the end of the experiment. Furthermore, increasing sandprawn abundance induced a phytoplankton sizebased shift from pico- to nano dominance, with nanophytoplankton contributing 17.76% at the beginning of the experiment, but shifting to 58.07% at the end of the experiment in the maximum sandprawn density treatment. Additionally, sandprawn presence had no significant impact on cryptophytes or Prochlorococcus-like algal abundance. These results demonstrate that sandprawns disproportionately impact certain groups and influence phytoplankton assemblages beyond biomass decline. These findings are novel as such discriminatory effects on pelagic assemblages have previously not been attributed to endobenthic deposit-feeding ecosystem engineers. This study therefore provides novel insights into mechanisms by which these organisms may alter coastal ecosystems and influence bentho-pelagic coupling processes. This is especially significant when viewed in the context of global change, where understanding the factors that influence phytoplankton dynamics are important for predicting ecosystem functioning under projected climatic conditions. Given the overall top-down impact of sandprawns on phytoplankton, this study supports the idea of sandprawns being effective nature-based tools that can mitigate the global challenge of eutrophication in coastal ecosystems. The results of this study ultimately emphasises the need for protection and conservation of sandprawns (and functionally similar endobenthic engineers) and their habitats from threats such as habitat loss.